Genetic determinants of the humoral immune response in MS. Issue 5 (September 2020) - Gasperi, Christiane; Andlauer, Till F.M.; Keating, Ana; Knier, Benjamin; Klein, Ana; Pernpeintner, Verena; Lichtner, Peter; Gold, Ralf; Zipp, Frauke; Then Bergh, Florian; Stangel, Martin; Tumani, Hayrettin; et al.
Abstract : Objective: In this observational study, we investigated the impact of genetic factors at the immunoglobulin heavy chain constant locus on chromosome 14 and the major histocompatibility complex region on intrathecal immunoglobulin G, A, and M levels as well as on B cells and plasmablasts in the CSF and blood of patients with multiple sclerosis (MS). Methods: Using regression analyses, we tested genetic variants on chromosome 14 and imputed human leukocyte antigen (HLA) alleles for associations with intrathecal immunoglobulins in 1, 279 patients with MS or clinically isolated syndrome and with blood and CSF B cells and plasmablasts in 301 and 348 patients, respectively. Results: The minor alleles of variants on chromosome 14 were associated with higher intrathecal immunoglobulin G levels (β = 0.58 [0.47 to 0.68], lowest adjusted p = 2.32 × 10 −23 ), and lower intrathecal immunoglobulin M (β = −0.56 [−0.67 to −0.46], p = 2.06 × 10 −24 ) and A (β = −0.42 [−0.54 to −0.31], p = 7.48 × 10 −11 ) levels. Alleles from the HLA-B*07:02-DRB1*15:01-DQA1*01:02-DQB1*06:02 haplotype were associated with higher (lowest p = 2.14 × 10 −7 ) and HLA-B*44:02 with lower (β = −0.35 [−0.54 to −0.17], p = 1.38 × 10 −2 ) immunoglobulin G levels. Of interest, different HLA alleles were associated with lower intrathecal immunoglobulin M (HLA-C*02:02, β = −0.45 [−0.61 to −0.28], p = 1.01 × 10 −5 ) and higher immunoglobulin A levels (HLA-DQA1*01:03-DQB1*06:03-DRB1*13:01 haplotype, β = 0.40 [0.21 to 0.60], p = 4.46 × 10 −3 ). The impact of HLA alleles on intrathecal immunoglobulin G and M levels could mostly be explained by associations with CSF B cells and plasmablasts. Conclusion: Although some HLA alleles seem to primarily drive the extent of humoral immune responses in the CNS by increasing CSF B cells and plasmablasts, genetic variants at the immunoglobulin heavy chain constant locus might regulate intrathecal immunoglobulins levels via different mechanisms.